2017
DOI: 10.18632/oncotarget.17429
|View full text |Cite
|
Sign up to set email alerts
|

Association between tea consumption and risk of cognitive disorders: A dose-response meta-analysis of observational studies

Abstract: BackgroundThe epidemiological evidence for a dose-response relationship between tea consumption and risk of cognitive disorders is sparse. The aim of the study was to summarize the evidence for the association of tea consumption with risk of cognitive disorders and assess the dose-response relationship.MethodsWe searched electronic databases of Pubmed, Embase, and Cochrane Library (from 1965 to Jan 19, 2017) for eligible studies that published in the international journals. A random-effects model was used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 77 publications
4
35
0
Order By: Relevance
“…Tea consumption could linearly decrease the risk of cognitive disorders by 6%, 19%, 29% at 100 mL per day (0.94, 0.92–0.96), 300 mL per day (0.81, 0.74–0.88), and 500 mL per day (0.71, 0.62–0.82) . A linear association was also found between tea consumption and Parkinson's disease (PD), as the smoking‐adjusted risk of PD was lowered by 26% with two cups per day .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Tea consumption could linearly decrease the risk of cognitive disorders by 6%, 19%, 29% at 100 mL per day (0.94, 0.92–0.96), 300 mL per day (0.81, 0.74–0.88), and 500 mL per day (0.71, 0.62–0.82) . A linear association was also found between tea consumption and Parkinson's disease (PD), as the smoking‐adjusted risk of PD was lowered by 26% with two cups per day .…”
Section: Resultsmentioning
confidence: 95%
“…Tea consumption seemed to be associated with a reduced risk of cognitive disorders; dose–response analysis showed a 26% lower risk of developing PD at two cups a day (0.74, 0.61–0.89) . Recently, a double‐blind RCT conducted in individuals with Down's syndrome showed that EGCG and cognitive training for 12 months was more effective than placebo and cognitive training at improving visual recognition memory, inhibitory control, and adaptive behavior .…”
Section: Discussionmentioning
confidence: 99%
“…104,105 In addition, in a meta-analysis of 17 independent observational studies, tea consumption was found to have an inverse linear relationship with the incidence of cognitive disorders. 6 Other observational studies have also shown that green and black tea consumption is related to a lower risk of experiencing cognitive impairment. 106,107 Tea consumption has further been found to independently reduce the risk for experiencing depression 108 and may have a protective effect against Parkinson's disease.…”
Section: Effects Of Polyphenols On Cognitionmentioning
confidence: 98%
“…Polyphenols from various food sources such as cocoa, coffee, tea, and apples have been associated with various healthrelated benefits, including in cardiovascular disease and type 2 diabetes. [4][5][6][7][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Possible mechanisms include effects on blood pressure, endothelial function, glucose metabolism, inflammation, oxidative stress biomarkers, platelet function, and cholesterol, as well as indirect effects mediated by interaction with the gut microbiome. 20,21 A portion of the evidence describing the role of polyphenols in cardiovascular health comes from epidemiologic studies involving different dietary patterns and intake of certain classes of foods.…”
Section: Effects Of Polyphenols On Cardiometabolic Healthmentioning
confidence: 99%
See 1 more Smart Citation